Physical workability as the base of students’ functional potentials - I.I. Samokih (Physical Education of Students, 2016)
Purpose: to assess the level of students’ physical workability and find its connection with physical fitness. Material: we tested 150 students (86 girls and 64 boys) of 17-19 years’ age. All students were in main health group. The students fulfilled test on stationary bicycle. The complex of tests for physical fitness was used. Results: it was found that boys’ physical workability results were better than girls’. Analysis of correlation matrix showed that physical workability parameters had close correlations with physical workability. Exception was only some pedagogic tests for explosive power of arms and torso as well as flexibility. Conclusions: physical workability indicators were within age and gender standards. Analysis of correlations showed that physical workability parameters substantially influence on results of control tests for physical fitness.